Development of Voriconazole Proliposome Based Dry Powder for Inhalation: A Design of Experiment Approach - Sanjeevani Deshkar; Alisha Vas; Roshani Pagar; Prabhanjan Giram; Asha Thomas; Vaishali Undale (Pharmaceutics)
The present investigation aimed to formulate and optimize sustained release proliposome dry powder for inhalation of Voriconazole (VZ) and its in vitro and in vivo evaluation. The proliposome-based dry powder for inhalation was formulated by spray drying technique using Phospholipon 90H and cholesterol in the lipid phase, mannitol as a carrier, and L-leucine as a dispersing agent. A face-centered central composite design was used to study the influence of factors on responses, vesicle size, VZ entrapment efficiency, and drug release. The optimized formulation was further characterized by FTIR, FESEM, DSC, XRD, and evaluated for in vitro drug release, in vitro aerosol deposition, and in vivo lung retention study in Wistar rats. For the optimized batch F-5 proliposome formulation, vesicle size was observed as 191.7 ± 0.049 nm with PDI 0.328 ± 0.009, entrapment efficiency as 72.94 ± 0.56%, and cumulative drug release after 8 h of dissolution was 82.0 ± 0.14%. The median mass aerodynamic diameter (MMAD) generated by optimized formulation F5 was significantly lower (3.85 ± 0.15 µm, p < 0.0001) as compared to spray-dried voriconazole (SD-VZ) (8.35 ± 0.23 µm). In vivo studies demonstrated a profound enhancement in lung retention (3.8-fold) compared to SD-VZ and oral VZ dispersion. Conclusively, proliposome formulation of voriconazole is a plausible and convincing approach for pulmonary fungal infections, considering its sustained release behaviour and prolonged lung retention.